(untitled) (Research, Society and Development, 2022)
Introduction: Diabetic foot ulcer is a local wound in patients with diabetes. Ozone therapy is becoming a treatment option as it accelerates healing. Objective: To verify the effectiveness of ozone therapy for the treatment of diabetic foot ulcers. Methodology: We performed searches in PubMed, SciELO, LILACS, MEDLINE, Web of Science and CINAHL databases until October 2021. The search included article references and clinical trial registry websites without limitation of language or publication date. Randomized and non-randomized clinical trials addressing ozone therapy in patients with diabetic foot ulcers were included. The Risk of Bias assessment tool and the Review Manager software, version 5.4 were used. Results: Six randomized and non-randomized clinical trials met the inclusion criteria (608 patients). Only two studies were considered to be at low risk of bias, with adequate randomization, allocation concealment, and blinded evaluation of results. One study compared two IPC regimens where there was evidence of a statistically significant treatment effect in favor of the rapid IPC regimen (hazard ratio 0.74, 95% CI 0.56 to 0.90). Five trials evaluated CPI as adjunctive therapy to standard therapies and agreed that CPI increases the rate of ulcer healing and a higher cure rate. Two trials evaluated CPI alone compared to other therapies. Conclusion: Ozone therapy for diabetic foot ulcers has been shown to be effective as an adjunct to standard treatment, although the included studies were classified as having a high risk of bias.